2017
DOI: 10.1007/s12182-017-0184-z
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of market reform on the market penetration of natural gas-fired electricity and renewable energy in China

Abstract: Natural gas-fired electricity (NGFE) is expected to play a more important role in the future due to its characteristics of low pollution, high efficiency and flexibility. However, its development in China is impeded by its high regulation price compared with coal power. Market reform is therefore of vital importance to promote the penetration of NGFE. The objective of this study is to analyze the impacts of market reform and the renewable electricity (RE) subsidy policy on the promotion of NGFE and RE. A dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There are sudden changes in the series when the statistic values drift up or down from the threshold, which define the upper and lower bounds for the drifts. The value of the threshold D* is estimated from 10,000 replicates of series of T independent N (0, 1) observations for the desired p = 0.95, following the same procedure introduced by Inclán and Tiao [21]. If the value of IT is bigger than a threshold given, the null hypothesis is rejected, and the value of k * is taken as the break date with high probability.…”
Section: Iterative Cumulative Sums Of Squares (Icss) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are sudden changes in the series when the statistic values drift up or down from the threshold, which define the upper and lower bounds for the drifts. The value of the threshold D* is estimated from 10,000 replicates of series of T independent N (0, 1) observations for the desired p = 0.95, following the same procedure introduced by Inclán and Tiao [21]. If the value of IT is bigger than a threshold given, the null hypothesis is rejected, and the value of k * is taken as the break date with high probability.…”
Section: Iterative Cumulative Sums Of Squares (Icss) Methodsmentioning
confidence: 99%
“…Meng (2016) claimed that reform caused a downshift to the "natural" generation efficiency curve of the thermal power industry [19]. Zhu and Yan et al (2017) [21] and [22] analyzed the impacts of renewable electricity promotion. They found that market reform not only promoted the penetration but also increased the utilization ratio of renewables significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This means the end treatment devices of China's adipic acid producers that were shut down in 2013 could be put back into operation in 2020. The technology penetration rate will increase to 60% in 2050 (Zhu et al 2017). Correspondingly, the efficiency of technology decomposition will gradually increase from 88% in 2020 to 98%.…”
Section: Appropriate N 2 O Abatement Scenario (Anas)mentioning
confidence: 99%